PERAN ELEMEN ALAM PADA SEQUENCE RUANG IBADAH STUDI KASUS MASJID BAHRUL ULUM, TANGERANG SELATAN - Hendola, Feby; Safitri, Ratna; Purisari, Rahma (Universitas Atma Jaya Yogyakarta, 2018)
Abstract: Sacred places are often characterized by architectural elements and arrangement of certain landscapes to form a different impression from the surroundings. Architecture is able to form space symbolically sacred through the arrangement that directs the congregation in worship. The natural elements in the landscape have an important function in forming the beauty that reminds human relations with the universe. Writing shows an understanding of the relationship between elements of nature (land, water, air, and light) with elements of architectural design in a place of worship. The case is Masjid Bahrul Ulum (MBU) in South Tangerang. MBU has a beautiful landscape, which supports the atmosphere from outside to inside the building. The researcher analyzed the role of natural elements in worship activities which were felt starting from the entrance of the mosque, the courtyard, the terrace, the place of ablution to the main worship hall. The search results show, the role of significant natural elements in the worship space sequence becomes a symbol as well as forming an atmosphere.Keywords: religious architecture, landscapes, mosques, prayer rooms, sacred.Abstrak: Tempat sakral sering ditandai dengan elemen arsitektur dan penataan lanskap tertentu hingga membentuk kesan yang berbeda dengan sekitarnya. Arsitektur mampu membentuk ruang menjadi sakral, secara simbolik melalui penataan yang mengarahkan jemaah dalam beribadah. Elemen-elemen alam pada lanskap memiliki fungsi penting dalam membentuk keasrian yang mengingatkan hubungan manusia dengan semesta. Tulisan ini merupakan upaya memahami keterkaitan antara elemen alam—tanah, air, udara, dan cahaya—dengan elemen perancangan arsitektur pada tempat ibadah yang mengarahkan umat dalam beribadah. Kasus peneliti adalah Masjid Bahrul Ulum (MBU) di Tangerang Selatan. MBU memiliki lanskap yang asri, sehingga mendukung suasana tentram hingga ke dalam bangunan. Peneliti menganalisis peran elemen alam dalam kegiatan peribadatan yang dirasakan mulai dari masuk lingkungan masjid, pelataran, teras, tempat wudu hingga ruang peribadatan utama. Hasil penelusuran menunjukkan, peran elemen alam dalam sequence ruang ibadah menjadi simbol sekaligus pembentuk suasana.Kata Kunci: arsitektur religius, lanskap, masjid, ruang ibadah, sakral.